A Human Liver‐on‐a‐Chip Platform for Modeling Nonalcoholic Fatty Liver Disease - Soufian Lasli; Han‐Jun Kim; KangJu Lee; Ceri‐Anne E. Suurmond; Marcus J. Goudie; Praveen Bandaru; Wujin Sun; Shiming Zhang; Ni‐Yuan Zhang; Samad Ahadian; Mehmet R. Dokmeci; Junmin Lee; et al. (2019)
The liver possesses a unique microenvironment with a complex internal vascular system and cell-cell interactions. Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease, and although much effort has been dedicated to building models to target NAFLD, most in vitro systems rely on simple models failing to recapitulate complex liver functions. Here, an in vitro system is presented to study NAFLD (steatosis) by coculturing human hepatocellular carcinoma (HepG2) cells and umbilical vein endothelial cells (HUVECs) into spheroids. Analysis of colocalization of HepG2-HUVECs along with the level of steatosis reveals that the NAFLD pathogenesis could be better modeled when 20% of HUVECs are presented in HepG2 spheroids. Spheroids with fat supplements progressed to the steatosis stage on day 2, which could be maintained for more than a week without being harmful for cells. Transferring spheroids onto a chip system with an array of interconnected hexagonal microwells proves helpful for monitoring functionality through increased albumin secretions with HepG2-HUVEC interactions and elevated production of reactive oxygen species for steatotic spheroids. The reversibility of steatosis is demonstrated by simply stopping fat-based diet or by antisteatotic drug administration, the latter showing a faster return of intracellular lipid levels to the basal level.